Formulation and Evaluation of in Vitro Anti-Inflammatory and Anticoagulant Efficacy of Tulasi Oil – A Siddha Polyherbal Formulation - Dr. S. Yavanarani; Dr. R. Selvakumar; Dr. M. Sathiyabama (International Journal of Pharma and Bio Sciences, 2022)
Inflammation is a normal defensive response to tissue damage caused by physical injury and harmful chemicals and currently, management of this condition is by the non-steroidal anti-inflammatory drugs (NSAIDs), which have various adverse effects. Over activity of the coagulation cascade (hypercoagulation) increases the risk of thrombosis formation leading to thromboembolism which in turn leads to ischemia by blocking blood flow and damaging the organs. Siddha formulations afford an incredible improvement in medical practice against various metabolic and lifestyle disorders. Hence, the present study was to evaluate the preliminary phytochemicals and in vitro anti-inflammatory potential of Tulasi oil (TO) against the HRBC membrane stabilization assay, egg albumin denaturation assay and the in vitro anticoagulant analysis. Tulasi oil appears to contain chemical constituents such as alkaloids, flavonoids, steroids, triterpenoids, tannins, phenols, proteins, anthocyanins and saponins. The concentration of 250 μg/ml of Tulasi oil has exhibited a maximum percentage of haemolysis (86.42 ± 0.25%) and albumin (protein) denaturation (81.15±0.82%) while the same concentration (250 μg/ml) of standard drug of hydrocortisone represented the haemolysis of 88.48 ± 0.33% and Diclofenac sodium showed 87.84±0.67 % of protein denaturation. For anticoagulant activity, the concentration of 20 mg/ml of tulasi oil showed maximum anti-coagulant activity of (1227 sec) and a minimum of 686 sec in 5 mg/ml. The standard drug EDTA and Sodium citrate showed better anti-coagulant activities of more than 30 minutes i,e., 2253 and 2156 minutes, respectively. The result of the work indicates that the polyherbal formulation of Tulasi oil has possessed remarkable in vitro anti-inflammatory and anticoagulant potential and can be applied as an alternative in the treatment of various inflammatory and cardiovascular complications.